Pandangan Konsumen Ibu PKK di Semarang terhadap Kehadiran Apoteker dalam Pelayanan Kefarmasian di Apotek - Sujono, Rosid; Sabiti, Farrah Bintang (Universitas Muhammadiyah Surakarta)
The existence of pharmacies is needed by the community, considering the higher number of morbidity which has an impact on the need for drugs. These phenomena make the pharmacists have to continue to exist and the community continues to visit and receive pharmaceutical services. The aim of this study was to describe the views and expectations of consumers towards the presence of Pharmacists in pharmacy services in Semarang. The descriptive survey research involved respondents from PKK with age of 40 - 60 years, who could read and write, consumers had visited the Pharmacy to redeem prescriptions or bought medicine and without distinguishing the respondent from the first time or the customer often visited the Pharmacy. The study was conducted in the city of Semarang with a total of 55 respondents. The results showed that almost all respondents (94.5%) visited the Pharmacy more than three times a month, with the biggest goal being to redeem recipes for children or families by 92.7%. Consumers’ views on the presence of mandatory pharmacists in pharmacies are 94.5% and pharmacists' expectation of providing pharmaceutical services 67.2%. Consumer expectations for the presence of pharmacists in pharmacies are 92.7%, expectation of meeting Pharmacists at 70.9%. Consumer experience about pharmaceutical services in the form of information on drug use amounts to (80%), side effects (65.4%) as well as how to store and dispose of drugs (52.7%.). Consumers expect the presence and can meet the Pharmacist at the Pharmacy so that they will get direct services in the form of consultation and counseling about drugs by the Pharmacist.